2022
DOI: 10.3390/ijms232315088
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Aldose Reductase in Beta-Amyloid-Induced Microglia Activation

Abstract: The occurrence of Alzheimer’s disease has been associated with the accumulation of beta-amyloid (β-amyloid) plaques. These plaques activate microglia to secrete inflammatory molecules, which damage neurons in the brain. Thus, understanding the underlying mechanism of microglia activation can provide a therapeutic strategy for alleviating microglia-induced neuroinflammation. The aldose reductase (AR) enzyme catalyzes the reduction of glucose to sorbitol in the polyol pathway. In addition to mediating diabetic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 63 publications
(82 reference statements)
1
8
0
Order By: Relevance
“…Furthermore, inflammation results in increased accumulation of ROS production which contributes to inflammatory cytokine secretion 68 . AR inhibition can alleviate oxidative stress by attenuating ROS and phagocytotic activity in microglial cells as recently reported by our group 67 . Published studies showed that activated microglia migrate into the inner nuclear or outer nuclear layer of the retina 9 , 69 , where the major neuronal cells reside.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Furthermore, inflammation results in increased accumulation of ROS production which contributes to inflammatory cytokine secretion 68 . AR inhibition can alleviate oxidative stress by attenuating ROS and phagocytotic activity in microglial cells as recently reported by our group 67 . Published studies showed that activated microglia migrate into the inner nuclear or outer nuclear layer of the retina 9 , 69 , where the major neuronal cells reside.…”
Section: Discussionsupporting
confidence: 68%
“…1 D) 38 , 63 . Additionally, Sorbinil has been previously reported to attenuate secretion of IL-1β in macrophages and activation of JNK and p38 66 , 67 . As Sorbinil does not affect BV2 cell viability, the attenuation of microglial distribution is unlikely caused by the cytotoxicity of Sorbinil (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to highlighting the role of potential therapeutic candidates for neuroinflammation in AD patients, the study has opened the way to an even broader understanding of the role of microglia as an inflammation inducer in AD; however, a full understanding of the role of microglia as a cellular inflammatory factor requires detailed research [ 86 ]. Huang et al, came to similar conclusions, identifying microglia as a factor for which understanding its function and activation can help determine how to neutralize inflammation in Alzheimer’s patients [ 87 ]. The excessive phagocytosis of amyloid plaques by microglia cells has been shown to play an important role in the penetration of β-amyloid into healthy brain regions of AD patients.…”
Section: Inflammatory Processes In Alzheimer’s Diseasementioning
confidence: 91%
“…The excessive phagocytosis of amyloid plaques by microglia cells has been shown to play an important role in the penetration of β-amyloid into healthy brain regions of AD patients. In vitro studies conducted by the authors showed that, along with the penetration of β-amyloid into healthy regions of neural tissue, microglia furthermore produce a large amount of pro-inflammatory cytokines such as IL-6, which further causes the inflammatory involvement of healthy neurons in AD patients [ 87 ].…”
Section: Inflammatory Processes In Alzheimer’s Diseasementioning
confidence: 99%
“… 81 , 82 Aldose reductase activity is significantly and systemically increased with hyperactivation of the sorbitol pathway in diabetes. 83 This leads to insulin resistance, resulting in widespread oxidative stress and increased inflammatory cytokines. The insulin receptor signaling system plays an important role in maintaining normal brain and cognitive functions 84 by regulating GLP-1 receptors, 84 , 85 insulin receptor substrate (IRS) receptors.…”
Section: Introductionmentioning
confidence: 99%